Evaluation of Attractiveness of Residential Markets in Poland - Żelazowski, Konrad (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
Residential market fulfills basic needs for security and shelter. The extent and quality of satisfying housing needs is an essential determinant of local market attractiveness and competitiveness. The aim of the paper is verification of housing attractiveness of regional capital cities in the years 2005-2011. For ranking purposes linear ordering methods were applied.